Experimental investigation on acoustic performance of coir fiber and rice husk acoustic panels. (15th March 2023) - Lekshmi, M.S.; Vishnudas, Subha; Anil, K.R.
Highlights: Eco-friendly, flame-resistant acoustic panel for low frequency sound absorption. Utilization of coir fiber and rice husk wastes as fibro-granular material for acoustic panel. Incorporation of RHA-replaced cement binder constituting 70% by weight of fibro-granular material. Around 86 % sound waves are absorbed within the frequency domain 500 Hz–5000 Hz. Noise reduction coefficient at four octave bands (250 Hz, 500 Hz, 1000 Hz and 2000 Hz) was 0.76. Abstract: Natural fibers, when used as passive sound absorbers, appear to be effective in absorbing medium and high frequency sound waves, but are weak in absorbing low frequency sound waves; sometimes a major challenge to design engineers and architects. This study investigates the possibility of using fibro -granular acoustic panel for the absorption of low frequency sound waves through an experimental approach. The incorporation of fibrous materials, coir fiber and granular material, rice husk combined with rice husk ash-replaced cement binder in these panels reduces the toxicity of commonly used binders such as phenol formaldehyde, polyester foams and polyurethane. The sound absorption coefficient of these panels was tested in an impedance tube and also in an anechoic room. The flame resistance of the fibro-granular material was also tested. The results show that the developed panels with density 200 kg/m 3 are effective in absorbing both low and high frequency sound waves within the acoustic frequency range 100 Hz −5000 Hz with a noise reduction coefficient > 0.4.The sound absorption coefficient of these panels was compared with that of commercial sound absorbers and was found to be better. In addition, significance of parameters influencing low frequency sound absorption of these panels were determined statistically. The eco-friendly acoustic panel made of agricultural residues does not require large capital investments. On the other hand, the disposal of these agricultural residues would incur operational cost coupled with health hazards. The incorporation of these waste materials in this eco-friendly acoustic panel would thus be economically beneficial to our society.